Efektifitas Pembentukan Peraturan Daerah Di Kabupaten Batang Hari Di Tinjau Dari Peraturan Menteri Dalam Negeri Nomor 80 Tahun 2015 Tentang Pembentukan Produk Hukum Daerah - Pratiwi, Dita Ayudia; Hardiyanti, Hardiyanti; Manery, Nugrah Gables (Programs Study Outside the Main Campus in Law Pattimura University ARU Islands Regency, 2023)
This study aims 1) to find out how effective the formation of regional regulations for Batang Hari Regency is based on the Regulation of the Minister of Home Affairs Number 80 of 2015 concerning the Establishment of Regional Legal Products. 2) To find out the inhibiting factors in the formation of regional regulations in Batang Hari Regency. The type of research is empirical juridical. The procedure for sampling is done by purposive sampling. Then the analysis of the data obtained, namely primary data and secondary data collected is drawn into a conclusion inductive method, namely from general data formulated in the form of questions. The results show that the formation of regional regulations in Batang Hari Regency is based on the Minister of Home Affairs Regulation Number 80 of 2015 concerning the Establishment of Regional Legal Products, the proposed Ranperda can be submitted by the regional government or DPRD. With the existence of local governments, it is expected to be effective in the practice of making local regulations by adjusting the interests of the community. The formation of regional regulations is required to prioritize the interests of the community, so it is hoped that there will be maximum cooperation between agencies related to the regional government so as to produce a regional regulation that has aspects of justice and legal certainty for the people of Batang Hari Regency.